The Political Economy of Audiences in Indonesia's Shopee Ecosystem: Commodification, Consumption, and Production of Meaning in the Digital Era - Intan Fuji Lestari; Rusadi, Udi (Indonesian Scientific Publication, 2024)
This study discusses how Shopee manages user data and digital features to commodify audiences and create structured consumption patterns through gamification and algorithms in the era of digital capitalism. The main objective of this study is to analyze Shopee's strategy in utilizing data and interactive features to increase consumption while building social relations that benefit the platform. Using a media political economy approach, qualitative research through literature review, this study explores the interaction between users, algorithms, and features such as Shopee Live, Feed, and Games. The study results show that data-based personalization and gamification strategies increase loyalty and create user dependence on the platform. In conclusion, Shopee has succeeded in maximizing profits through data exploitation. Still, it has also created an imbalance of power in managing user data, limiting its control over personal information.